Impact of age on the circadian visual system and the sleep-wake cycle in mus musculus - Dorela D. Shuboni-Mulligan (Nature Portfolio, 2021)
Abstract Age plays a critical role in disease development and tolerance to cancer treatment, often leading to an increased risk of developing negative symptoms including sleep disturbances. Circadian rhythms and sleep become disrupted as organisms age. In this study, we explored the behavioral alterations in sleep, circadian rhythms, and masking using a novel video system and interrogate the long-term impact of age-based changes in the non-image forming visual pathway on brain anatomy. We demonstrated the feasibility and utility of the novel system and establish that older mice have disruptions in sleep, circadian rhythms, and masking behaviors that were associated with major negative volume alterations in the non-imaging forming visual system, critical for the induction and rhythmic expression of sleep. These results provide important insights into a mechanism, showing brain atrophy is linked to age in distinct non-image forming visual regions, which may predispose older individuals to developing circadian and sleep dysfunction when further challenged by disease or treatment.